El "Forum Augustum": reflexiones sobre su configuración arquitectónica y su funcionalidad judicial (a propósito de la "Basílica Antoniarum Duarum") - Ventura Villanueva, Ángel (ROMULA, 2012)
The aim of this work is to give new arguments, in no case conclusive one by one but meaningful in their whole, regarding the original architectural configuration of Forum Augustum in Rome. Reflections like that lead us to defend the existence of a double apse basilical-space closing the SW short flank of the square, which faces the façade of Mars Ultor temple, as La Rocca suggested. Within those apses we must locate, through the first century AD, the tribunals from both the urban praetor and the peregrine praetor, which are mentioned in vadimonial documents retrieved from Pompeii and Herculaneum. This space or "basilica" was in use until a first domicianean reform in which, due to the Forum Transitorium construction, the SE apse would have been suppressed, moving the peregrin pretor’s tribunal to the so-called Porticus Absidato. Soon after, they would proceed to the complete and definitive demolition of the basilical building because of the construction of Forum Traiani, whose Basilica Ulpia would enclose the urban pretor’s tribunal, re-systematizing and enlarging the augustean square at the same time. This monument short life, hardly one hundred years, justifies the silence of literary sources regarding its existence and official denomination, although some epigrafic sources point out "Bosilica Antoniarum Duarum" as its popular name, probably due to the evergetical assistence of Augustus’ nieces in its ornamentation.